Priming Matrix – Collective Nonconscious Programming - Ilievska, Angelina; Naum Ilievski (European Journal of Multidisciplinary Studies, 2020)
Contemporary sociology, and especially social psychology, explores the mechanisms of priming, automaticity, and their effects on social behavior. Priming matrix is a new concept, a phrase semantically coined by the author in order to explain such complex socio-psychological phenomena in the area of social cognition. This study makes an analyses and description of the dynamics and mechanisms of the programming from a socio-psychological aspect, Transactional analysis, and the perspective of Christian psychotherapy. Methodologically, new concepts are applied: priming matrix and types of representations (Ilievska) with its operational elements (stimulus, prime, representation, subliminal level), and the concepts: awareness and collective nonconscious schemes (Ilievski, 2015), which are described as an opposite of the natural way of life, the personal autonomy and the real freedom. Each person has a basic need for relation, psychological organization, and structure. In its foundation lies the creation of basic mental constructs, socio-cognitive schemes, which have a neurobiological ground. In addition, human behavior can be programmed, nonconsciously, on multiple levels: individual, collective, global, through the complex psychological processes, modeling and conditioning, to the more subtle forms of priming, creating passive automatic social behavior.